Design, synthesis and evaluation of 3, 4-dihydroxybenzoic acid derivatives as antioxidants, bio-metal chelating agents and acetylcholinesterase inhibitors. (February 2015) - Friggeri, Laura; De Vita, Daniela; Pandolfi, Fabiana; Tortorella, Silvano; Costi, Roberta; Di Santo, Roberto; Scipione, Luigi
Abstract Metal ions, especially copper, zinc and iron, play an important role in the neurodegeneration process because they can affect protein misfolding, leading to the formation of the amyloid deposits and oxidative stress leading to reactive oxygen species (ROS). Here we report the synthesis and evaluation as antioxidant and metal chelating agents of 3, 4-dihydroxybenzoic acid derivatives. Synthesized compounds were tested by the 2, 2-diphenyl-2-picrylhydrazyl (DPPH) method showing a radical scavenging ability (EC50 = 0.093–0.118 μM) higher than Trolox used as reference. Furthermore, these compounds were able to bind both iron and copper, especially the iron (III), by the formation of hexa-coordinated complexes. Synthesized compounds were tested to evaluate their ability to inhibit acetyl- and butyryl-cholinesterase; the obtained results have demonstrated that they are selective inhibitors of AChE (Ki = 1.5–18.9 μM) and result weakly active versus butyrylcholinesterase (BChE).